Fatal abrin poisoning by injection. (1st February 2021) - Rinner, Ginger R.; Watkins, Sarah A.; Shirazi, Farshad Mazda; Fernández, Miguel C.; Hess, Greg; Mihalic, Jason; Runcorn, Susan; Waddell, Victor; Ritter, Jana; Reagan-Steiner, Sarah; Thomas, Jerry; Yip, Luke; et al.
Abstract: Abrin is a toxin of public health concern due to its lethality, lack of antidote, and potential for use as a bioterrorism agent. Possible routes of exposure include ingestion, inhalation, and injection. Onset of symptoms is often delayed, even in severe cases. In fatal cases, death occurs from multi-organ failure. We describe the clinical course, laboratory, and pathologic findings in a case of fatal human poisoning associated with abrin injection. The Abrus precatorius seeds in this case were obtained via the internet. The Centers for Disease Control and Prevention's Laboratory Response Network detected abrine in the urine confirming abrin exposure in this fatal poisoning.